Significant decrease in plasmad‐dimer levels and mean platelet volume after a 3‐month treatment with rosuvastatin in patients with venous thromboembolism. Issue 7 (28th April 2022) - Alirezaei, Toktam; Sattari, Haniyeh; Irilouzadian, Rana
Abstract: Background: Inflammation has been considered as a possible mechanism for the initiation and recurrence of venous thromboembolism (VTE). Statins have anti‐inflammatory and potential immune‐modulatory effects, but their effect on plasmad ‐dimer levels is controversial. Hypothesis: In this study, we aimed to evaluate the impact of rosuvastatin on D‐dimer and other inflammatory serum markers in VTE patients. Methods: We conducted a prospective, randomized study on 228 patients with VTE. Control group received conventional treatment (warfarin or rivaroxaban), whereas rosuvastatin‐intervention group received rosuvastatin 10 mg daily, in addition to their conventional treatment for 3 months. Serum markers were extracted from both groups at the baseline and 3 months after the beginning of treatment. Results: After 3 months, in patients of the intervention group, there was a statistically significant decrease in levels ofd ‐dimer and mean platelet volume (MPV) but no significant change in neutrophil‐to‐lymphocyte ratio and platelet‐to‐lymphocyte ratio. Conclusions: Our results showed that a 3‐month treatment with 10 mg rosuvastatin daily can significantly decrease the plasma levels ofd ‐dimer and MPV, which would support a potential role of statins to reduce activated systemic inflammation among VTE patients. Such effects can be used to reduce the rate of recurrent VTE in these patients.